Composite Drug Delivery System Based on Amorphous Calcium Phosphate-Chitosan: An Efficient Antimicrobial Platform for Extended Release of Tetracycline - Anita Ioana Visan; Carmen Ristoscu; Gianina Popescu-Pelin; Mihai Sopronyi; Consuela Elena Matei; Gabriel Socol; Mariana Carmen Chifiriuc; Coralia Bleotu; David Grossin; Fabien Brouillet; Sylvain Le Grill; Ghislaine Bertrand; et al. (MDPI AG, 2021)
One major warning emerging during the first worldwide combat against healthcare-associated infections concerns the key role of the surface in the storage and transfer of the virus. Our study is based on the laser coating of surfaces with an inorganic/organic composite mixture of amorphous calcium phosphate-chitosan-tetracycline that is able to fight against infectious agents, but also capable of preserving its activity for a prolonged time, up to several days. The extended release in simulated fluids of the composite mixture containing the drug (tetracycline) was demonstrated by mass loss and UV-VIS investigations. The drug release profile from our composite coatings proceeds via two stages: an initial burst release (during the first hours), followed by a slower evolution active for the next 72 h, and probably more. Optimized coatings strongly inhibit the growth of tested bacteria (Enterococcus faecalis and Escherichia coli), while the drug incorporation has no impact on the in vitro composite's cytotoxicity, the coatings proving an excellent biocompatibility sustaining the normal development of MG63 bone-like cells. One may, therefore, consider that the proposed coatings' composition can open the prospective of a new generation of antimicrobial coatings for implants, but also for nosocomial and other large area contamination prevention.